English World 9 B1+ Work book - Bowen, Mary; Hocking, Liz; Wren, wendy (Oxford Macmillan, 2013)
English World is a stunningly visual ten-level course which will take children through from primary to secondary. Written by the authors of best-sellers Way Ahead and Macmillan English, English World combines best practice methodology with innovative new features for the modern classroom. Active whole-class learning is supported by interactive activities on the WB CD-ROM. Thorough grammar and skills work is applied in natural contexts in the real world, through dialogues and cross-curricular material. English World provides a complete package for today's teachers and students. Key features Innovative Teacher's DVD-ROM with teaching methodology videos, teacher training videos and interviews with the course authors as well as the complete digitised Student's Book with Answer Keys, accessible audio and zoomable activities Informative, cross-curricular and cross-cultural content means that students learn about the world through English The stories, topics and projects promote social values and citizenship Systematic skills support and extension in the Workbook helps students develop learning strategies Level 7 has a specially written Dictionary designed to ease the transition from primary to secondary education
Languages
2
Keywords: English language